Labour as a driver of enterprise success. (2nd November 2004) - Rogovsky, Nikolai; Sims, Emily
Is there a trade-off between treating employees well and succeeding in business? Many employers assume that treating employees well means higher labour costs and lower profits. But a number of companies have found that they can do well by their employees and also succeed in business. People-centred management practices can make organisations more successful. In many cases, they actually reduce labour costs; in others, increased labour productivity more than offsets the costs of improving the well-being of workers. People-centred management spans a range of issues, from hiring and recruiting to employee involvement and union relationships, and corresponds clearly to many of the basic principles enshrined in International Labour Standards (ILS), promoted by the International Labour Organisation (ILO). The article is based on the authors' book, Corporate Through People: Making the International Labour Standards Work for You.